Intraoperative polyuria following sevoflurane administration - Yang, N.C.; Wei, E.L.; Ani, A.A.C.; Kumaravadivel Dharmalingam, T.; Rajesh Kumar Muniandy (Gazi Universitesi, 2020)
Sevoflurane has been used widespread due to its favorable pharmacokinetic profile. It is used as a volatile anaesthetic agent in the operating theatre (OT), and a sedative agent in the intensive care unit (ICU). However, the use of sevoflurane is not without side effects. The following is a case report detailing a patient who developed polyuria following intraoperative use of sevoflurane. © Copyright 2021 by Gazi University Medical Faculty